2017
DOI: 10.1038/onc.2017.403
|View full text |Cite
|
Sign up to set email alerts
|

SPARCL1 suppresses osteosarcoma metastasis and recruits macrophages by activation of canonical WNT/β-catenin signaling through stabilization of the WNT–receptor complex

Abstract: Metastasis significantly reduces the survival rate of osteosarcoma (OS) patients. Therefore, identification of novel targets remains extremely important to prevent metastasis and treat OS. In this report, we show that SPARCL1 is downregulated in OS by epigenetic methylation of promoter DNA. In vitro and in vivo experiments revealed that SPARCL1 inhibits OS metastasis. We further demonstrated that SPARCL1-activated WNT/β-catenin signaling by physical interaction with various frizzled receptors and lipoprotein r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 49 publications
1
44
2
Order By: Relevance
“…The functional role of the Wnt signaling pathway in OS is not completely understood ( 23 ). A number of studies support the idea that the Wnt signaling pathway serves an anti-tumorigenic effect in OS ( 24 26 ), whereas other studies suggest that aberrant activation of the canonical Wnt signaling pathway serves an important role in OS initiation, maintenance and resistance to chemotherapy ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the Wnt signaling pathway in OS is not completely understood ( 23 ). A number of studies support the idea that the Wnt signaling pathway serves an anti-tumorigenic effect in OS ( 24 26 ), whereas other studies suggest that aberrant activation of the canonical Wnt signaling pathway serves an important role in OS initiation, maintenance and resistance to chemotherapy ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secreted protein acidic and rich in cysteine-like protein 1 (SPARCL1) is a member of the SPARC family, which is associated with various biological behaviors including osteoblast differentiation and development of cancers. Previous studies have suggested SPARCL1 as a potential tumor suppressor (5)(6)(7). Low SPARCL1 expression is associated with the development and progression of cervical cancer (8).…”
Section: Introductionmentioning
confidence: 98%
“…Low SPARCL1 expression is associated with the development and progression of cervical cancer (8). Zhao et al (5) detected that SPARCL1 was significantly down-regulated in human osteosarcoma cell lines and clinical tissue samples. Interestingly, a recent study revealed that SPARCL1 was strongly down-regulated by 6.4-fold in 594 ovarian cancer cases compared with eight normal ovaries and was suspected to contribute to tumor invasiveness (9).…”
Section: Introductionmentioning
confidence: 99%
“…Another patient displayed a RICTOR-CCDC152 fusion (Figure 5C and D). A fusion transcript RORA-LHFP composed of RORA exon 1 fused to LHFP exon 3 is shown in Figure 5E and F. The three fusion genes are speculated to be involved in tumor growth, as their partners have important roles in malignant diseases (24)(25)(26).…”
Section: Pseudogenes Are Involved In Formation Of Gene Fusionmentioning
confidence: 99%